The new Newbolt report : one hundred years of teaching English in England - Green, Andrew, 1969- (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2021)
This book offers a pivotal re-evaluation of English teaching one century on from The Newbolt Report of 1921, responding to this seminal work and exploring its impact on issues and contemporary aims of English teaching today. Bringing together a range of experts in English higher education, the book provides a twenty-first century inflection on the enduring issues highlighted by Newbolt's original report. It examines topics including the demands of assessment, the narrowing of the literary curriculum, the impact of education reform, targets related to social mobility, class and widening participation, as well as broader questions about the function of literature and the arts in education. Chapters also consider issues surrounding the promotion of community cohesion, diversity and how technological advances might reshape literary education. This unique re-evaluation of the achievements and findings of the New bolt Commission will be essential reading for those researching English education and the history of education.
Keywords: English language -- Study and teaching; English language -- Study and teaching -- Curricula; English language -- Study and teaching -- History; Education and state; EDUCATION / Educational Policy & Reform / General; EDUCATION / History